Rancang Bangun Aplikasi Monitoring Distribusi Barang Berbasis Web Pada PT. XYZ - Muhammad Arief Nur Hakim (mijournal.org, 2026)
PT. Selamat Sejahtera Sejati is one of the leading goods distribution companies in South Kalimantan. In its business operations, recording and monitoring the flow of goods distribution, product ordering by partner stores, and checking stock availability are still conducted manually and conventionally. These limitations cause several operational problems, such as discrepancies between customer orders and deliveries, stockouts during ordering due to the lack of real-time stock visibility, and difficulties in monitoring distribution fleets and customer receivables in an integrated manner. This study aims to design and develop a Web-Based Goods Distribution Monitoring Application to automate and integrate business processes among administrators, warehouse staff, delivery fleets, and customer stores. The software development methodology employed is the System Development Life Cycle (SDLC) Waterfall model with structured modeling using Data Flow Diagrams (DFD) and Enhanced Entity Relationships (EER). The application is implemented using PHP programming language and MySQL database. System validation is carried out using Black Box Testing covering all menu functionalities and multi-level user access rights. The test results demonstrate that all system features function 100% validly according to specifications, successfully minimizing ordering errors, facilitating real-time stock and fleet monitoring, and enhancing operational efficiency and transparency at PT. Selamat Sejahtera Sejati.